Biodegradation Technology of Organic and Inorganic Pollutants - Ferreira Mendes, Kassio; Nogueira de Sousa, Rodrigo; Cabral Mielke, Kamila (IntechOpen, 2022)
Bioremediation technologies for environments contaminated by organic and inorganic pollutants are a major focus of researchers and scientists worldwide. The chemical control of agricultural pests and advocacy for sustainable agriculture have led to the development of new paradigms in environmental remediation. This book covers recent advances in the bioremediation technology of organic and inorganic pollutants in the environment.